ISLAM DAN PEACE BUILDING - Deni Irawan (Religi: Jurnal Studi Agama-agama, 2014)
Islam is the religion of dialogue that offers a variety of ways to create peace and harmony. Islam teaches compassion, tolerance, and the importance of friendship. Dialogue is a key concept in conflict resolution and peace building. This paper deeply discusses about dialogue in Islam as tool for building a peaceful civilization.